Analysis of Pre-Service Teachers' ICT Competencies in Indonesia and Japan - Zaenuri , Zaenuri; Widiyatmoko, Arif; Subhan , Subhan; Nakamura, Daiki (Jurnal Pendidikan IPA Indonesia, 2026)
The development of Information and Communication Technology (ICT) has an impact on education 5.0, improving educators' competence in using technology to support learning. The purpose of this study is to analyze the ICT competence of pre-service teachers in Indonesia and Japan. The research method used in this study is a survey to obtain information about the ICT competence of pre-service teachers in Indonesia. The research sample comprised 317 teacher study program students from two universities. The research instrument was a 30-item questionnaire administered via Google Forms to assess pre-service teachers' ICT competence. The results showed differences in the ICT competencies of pre-service teachers in Indonesia and Japan. Indonesian and Japanese pre-service teachers differ in their abilities in aspects such as understanding, technical skills, and teacher professional development. The average results of pre-service teachers' ICT competence in Indonesia and Japan, by aspect, show differences. All averages for aspects of ICT competence are 3-5, indicating good or very good criteria. Based on the study's results, it can be concluded that the ICT competence of pre-service teachers in Indonesia and Japan falls into the good category.